IDENTIFIKASI FAKTOR PENENTU MOBILITAS DI KECAMATAN SUKARAJA - Alnur Fitria Ningsih; Hutapia Hutapia (Universitas Bengkulu, 2019)
This study aimed to analyze the charasteristics factors which are able to influence the workers decision to commit commuting migration in Sukaraja subdistrict of Seluma regency. This research is descriptive research that will analyze the effect charasteristics of wage, age , level of education, marriage, sex and land to the workers decision to commit commuting migration in Sukaraja subdistrict of Seluma regency. The research was conducted by an experimental apptoach using primary data. Samples were taken as 100 respondents in proportional random sampling with random sampling method. Analysis of the data used descriptive analysis . The results showed difference in charasteristics of wage, age , level of education, marriage, sex and land to influence the workers decision to commit commuting migration in Sukaraja subdistrict of Seluma regency.Keywords: commuting migration, wage, age , level of education, marriage, sex and land